2011
DOI: 10.1021/nn103362n
|View full text |Cite
|
Sign up to set email alerts
|

Protease-Sensitive, Polymer-Caged Liposomes: A Method for Making Highly Targeted Liposomes Using Triggered Release

Abstract: Liposomes have become useful and well-known drug delivery vehicles because of their ability to entrap drugs without chemically modifying them and to deliver them somewhat selectively to tumorous tissue via the enhanced permeation and retention (EPR) effect. Although useful, liposome preparations are still less than ideal because of imperfect specificity, slow release kinetics in the tumor, and leakiness prior to reaching the tumor site. Cancer-associated proteases (CAPs), which are differentially expressed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(80 citation statements)
references
References 25 publications
2
73
0
Order By: Relevance
“…Cancer-associated proteases are another set of enzymes that are upregulated in tumours and can be used to develop enzyme-sensitive NDDSs. For instance, conjugates composed of cholesterol, peptide and poly-acrylic acid were cleaved by a cancer-associated protease (urokinase) and induced rapid drug release in an in vitro model 93 .…”
Section: Stimuli-sensitive Nddssmentioning
confidence: 99%
“…Cancer-associated proteases are another set of enzymes that are upregulated in tumours and can be used to develop enzyme-sensitive NDDSs. For instance, conjugates composed of cholesterol, peptide and poly-acrylic acid were cleaved by a cancer-associated protease (urokinase) and induced rapid drug release in an in vitro model 93 .…”
Section: Stimuli-sensitive Nddssmentioning
confidence: 99%
“…Hariri and coworkers investigated the use of radiation to guide FePt nanoparticles to tumor sites using a short peptide that targets TIP-1 receptor, a receptor upregulated on endothelial cells in response to radiation-induced injury [94]. Basel and coworkers demonstrated that targeting ligands may not always be necessary for effective nanoparticle targeting via the exploitation of high concentrations of cancer-associated protease (CAP), such as urokinase plasminogen activator (uPA), matrix metalloproteases (MMPs), and some cathepsins, in dysplastic tissues [95]. In a radical shift of nanoparticle targeting strategy, Choi and Kennedy demonstrated that macrophages and human T cells could be loaded with gold nanoparticles (AuNPs) and used to deliver those AuNPs to tumor sites [96, 97].…”
Section: Chimeras Multifunctionalization and Other Unconventional Amentioning
confidence: 99%
“…The altered levels of certain local enzymes in cancer tissues, such as matrix metallo proteinases (MMPs), human leukocyte elastase (HLE) and cancer-associated proteases (CAPs), have been the rationale to develop enzyme-triggered NPs for drug delivery [43]. Over-expressed levels of MMP2 and HLE are found in the tumor microenvironment, where they promote invasion, progression and metastasis of most human tumors by degrading the intercellular collagen matrix and extracellular matrix barrier, respectively [44-47].…”
Section: Enzyme-responsive Systemsmentioning
confidence: 99%